ANALISIS KINERJA KEUANGAN DAN MAKRO EKONOMI TERHADAP PROFITABILITAS PERBANKAN SYARIAH DI INDONESIA - Muhammad Irfan Pratama; Abdul Hakim (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Abstract: Banking profitability is influenced by several factors, especially from financial performance factors and macroeconomic factors, therefore the author conducted a study entitled Analysis of Financial and Macroeconomic Performance Against Islamic Banking Profitability in Indonesia. This study aims to analyze the effect of financial and macroeconomic performance on the profitability of Islamic banking in Indonesia. The data analysis uses the Error Correction Model (ECM). The results show that in the long run the variables of NPF, FDR, CAR, Interest Rates and Industrial Production Index affect ROA while for inflation and Covid-19 do not affect ROA. In the short term, only the FDR, CAR and Industrial Production Index variables have an effect on ROA, while the NPF, Inflation, Interest Rate and Covid-19 variables have no effect on ROA.